1. Let p and q be the following statements:
p: It is not April 17th
q: It is not Matt's birthday.
p⇒q is the conditional statement "If it is not April 17th, then it is not Matt's birthday."
the inverse of the conditional statement p⇒q is ¬p⇒¬q so we need to negate both p and q:
¬p: not p ≡ not (It is not April 17th) ≡ It is April 17th
¬q: not q ≡ not (It is not Matt's birthday) ≡ It is Matt's birthday
¬p⇒¬q: If (not p) then (not q) ≡ if (It is April 17th) then (It is Matt's birthday)
≡ "if It is April 17th then It is Matt's birthday"